Pengaruh Pembelajaran Video Berbasis White Board Animation Pada Materi Penjumlahan Dan Pengurangan Untuk Meningkatkan Hasil Belajar Siswa SD - Aslamyah, Nur; Hidayat, Rahman (Yayasan Pendidikan Intan Cendekia, 2023)
This study aims to determine the effect of white board animation- based video learning on addition and subtraction material to improve student learning outcomes of class II SDN 01 Pekat. This type of research is a quasi-experimental design. Data collection methods in this research are tests, documentation, and observation sheets. Data analysis was performed using quantitative analysis. Based on the results of data analysis and discussion in the research, it can be concluded that,